Analysis of the Influence of Work Culture, Work Experience and Work Ethics on Employee Work Discipline in Dinas Ketenagakerjaan Provinsi Sumatera Utara - Anggun Anugrah; Eli Delvi Yanti; Saimara A.M Sebayang (Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the influence of work culture, work experience, and work ethics on employee work discipline at the Manpower Office of North Sumatra Province. The research approach used is quantitative with an associative method. The sample in this study amounted to 43 honorary employees who were determined using a saturated sampling technique. This study was conducted from 2025. Data collection was carried out using a questionnaire to produce primary-quantitative data which was then processed with SPSS version 24 with a multiple linear regression method. The results of the study indicate that work culture partially has a positive and significant effect on employee work discipline at the Manpower Office of North Sumatra Province. Work experience partially has a positive and significant effect on employee work discipline at the Manpower Office of North Sumatra Province. Work ethics partially has a positive and significant effect on employee work discipline at the Manpower Office of North Sumatra Province. Work culture, work experience and work ethics simultaneously have a positive and significant effect on employee work discipline at the Manpower Office of North Sumatra Province. The results of the coefficient of determination test (Adjusted R Square) of 0.783 indicate that 78.3% of the variation in work discipline can be explained by work culture, work experience, and work ethics, while the remaining 21.7% is influenced by other factors outside the research model.